2019
DOI: 10.3389/fneur.2019.00857
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Functional Upper Extremity Motion

Abstract: Background: Functional upper extremity (UE) motion enables humans to execute activities of daily living (ADLs). There currently exists no universal language to systematically characterize this type of motion or its fundamental building blocks, called functional primitives. Without a standardized classification approach, pooling mechanistic knowledge and unpacking rehabilitation content will remain challenging. Methods: We created a taxonomy to characterize functional UE motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 48 publications
1
62
0
2
Order By: Relevance
“…We also generated confusion matrices to further characterize where ML algorithms are performing well (successful classification) vs. becoming confused (misclassification). In our analysis, we observed that NBC had limited success in differentiating between reaches and transports , functional primitives whose motion patterns are quite similar (12). The main difference between these primitives are grasp-related wrist motions (wrist extension and supination) occurring during reach (12).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We also generated confusion matrices to further characterize where ML algorithms are performing well (successful classification) vs. becoming confused (misclassification). In our analysis, we observed that NBC had limited success in differentiating between reaches and transports , functional primitives whose motion patterns are quite similar (12). The main difference between these primitives are grasp-related wrist motions (wrist extension and supination) occurring during reach (12).…”
Section: Discussionmentioning
confidence: 94%
“…In our analysis, we observed that NBC had limited success in differentiating between reaches and transports , functional primitives whose motion patterns are quite similar (12). The main difference between these primitives are grasp-related wrist motions (wrist extension and supination) occurring during reach (12). To accurately disambiguate these primitives with a lower-performing algorithm, we would emphasize [i.e., assign higher weights to (47)] data from the distal UE segment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Activities implement a therapeutic framework, which combines DDA with clinically valid therapeutic approaches for the target indication. For upper extremity (UE) rehabilitation, activities in CogniviveVR are based on a bottom-up approach, which starts with "essential components" of movement [13][14][15] and gradually builds up a patient's ability to perform complex ADL-like tasks. For example, an activity may start by requiring a patient to reach to an object and move it, but no grasping is required.…”
Section: Cognivivevr Therapeutic Frameworkmentioning
confidence: 99%